HOW TO RESPOND TO THE CHALLENGES OF ARTIFICIAL INTELLIGENCE: A COMPARATIVE ANALYSIS OF REGULATORY APPROACHES OF THE EUROPEAN UNION, CHINA, AND THE UNITED STATES - Dabić, Dragana; Stanković, Nevena (Serbian political thought, 2025)
The rapid development and implementation of artificial intelligence technology in various spheres of social activity confronts legal systems with the challenges of defining the protection of fundamental rights, liability for damage, and managing an acceptable level of risk to stimulate innovation. In the era of digital transformation, technology has become a new arena in which the interests of great powers are weighed and the contours of future global power are shaped. The regulation of artificial intelligence reflects the value, (geo)political, and (geo)economic priorities of prominent actors in this domain. The subject of the paper is a comparative analysis of the regulatory approaches of the European Union, the People's Republic of China, and the United States of America. The paper employs a qualitative study of the content of relevant strategic and normative documents to interpret the fundamental principles that underpin the selected regulatory frameworks. The main differences between them are identified, which point to internal socio-economic priorities, but also similarities that reveal global ambitions. The focus is on institutional dynamics, legislation in force, and ethical guidelines to overcome general comparisons dominant in contemporary public discourse. It is necessary to critically examine the overly simplistic view that the European approach to artificial intelligence places the protection of fundamental rights at the center stage; the American approach is dominated by the private sector and market dynamics, with excessive commercialization; while the Chinese approach is characterized by strong state control and strategic planning, along with the development of controversial surveillance systems. The implications of the observed divergent interests for the future of the ethical application of ubiquitous artificial intelligence are discussed, as well as the possibilities for eventual reconciliation of differences in order to achieve international harmonization of rules. By analyzing the specificities, but also the contradictions, of AI governance in large jurisdictions, the authors offer a rounded judgment on the (in)compatibility of value-based regulation with the pragmatic need to achieve technological supremacy. This allows for a deeper understanding of the positioning of great powers and European states embodied in the supranational Union in the global technological architecture, as well as contributing to the discussion on contemporary social challenges brought about by the seemingly unstoppable development of advanced technologies.
Keywords: EU; China; USA; artificial intelligence; regulatory approach; EU AI Act; Executive Оrder on Artificial Intelligence; Next Generation Artificial Intelligence Development Plan; technological race